The Modified Micro Environment Beans (Fabaceae) Storage and Effect to Behavior of Callosobruchusmaculatus Fab. (Coleoptera: Bruchidae). (September 2019) - Hakim, Lukmanul; Irhamni; Zainuddin; Makmur, T
Abstract: Irradiation is one element of the microclimate around the storage space can be controlled. Control of micro elements can be done using light. Beans are the second source of food after rice and wheat. Quantitative and qualitative losses during storage due to insect dominant.Callosobruchusmaculatus (Fab.) is a species of insect damage to beans during storage. This study aimed to manipulate the microenvironment of storage space by using a light color. This research was conducted in the laboratory of the Faculty of Agricultural Technology, SerambiMekkah University, Banda Aceh. Data collection and analysis using completely randomized design (CRD) factorial. The first factor to use four colors comprising light: red (L1), yellow (L2), green (L3) and white (L4). The second factor consists of three kinds of beans, namely: green beans (K1), soybean (K2), and red beans (K3) with 3 repetitions. The results showed an unpopular environment of C. maculatusFabricius in a room that was illuminated in white (L4). The highest eggs placement preference for C. maculatusFabricius on red beans (K3).